Online Marketing and Consumer Buying Behaviour of Electronic Products in the North Central Zone of Nigeria - Tyopine, Hanmaikyur (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2019)
This study examined effects of online marketing and consumer buying behaviour of electronic products in the north central zone of Nigeria. The population of this study comprised online marketers and online consumers in the seven states in north central zone of Nigeria. Because the population is infinite, a sample of 385 respondents were taken from marketers and the online consumers. Information was obtained from the respondents using a structured questionnaire. The data collected were analyzed using descriptive statistics such as frequency, simple percentage and the relationship between the variables of the model was tested using multiple linear regression analysis. The result of the regression analysis indicates that a negative relationship exist between perceived risk on consumer (PRK) and consumer buying behavior of electronic products in the north central zone of Nigeria (CBHV) and the relationship is not statistically significant (p>0.05). A positive relationship exist between perceived enjoyment (PEN) and consumer buying behavior of electronic products in the north central zone of Nigeria (CBHV) and the relationship is statistically significant (p<0.05). Perceived ease of use (PEU) was positively related to consumer buying behavior of electronic products in the north central zone of Nigeria (CBHV) and the relationship is statistically significant (p<0.05). Perceived usefulness (PUF) was negatively related to consumer buying behavior of electronic products in the north central zone of Nigeria (CBHV) and the relationship is not statistically significant (p>0.05). A positive relationship exist between perceived convenience (PCN) and consumer buying behavior of electronic products in the north central zone of Nigeria (CBHV) and the relationship is statistically significant (p<0.05). It was concluded that majority of the respondents who patronize online shopping adopt that because of the convenience and time saving factor they obtain from it. It was recommended among others that owners of online marketing platform should ensure that they make their website dynamic and user friendly so as to attract customers who will derive comfort and satisfaction transacting from the comfort of their homes.